Kairomones effect on parasitic activity of Trichogramma japonicum against rice yellow stem borer, Scirpophaga incertulas. (29th March 2020) - Murali‐Baskaran, Ramasamy Kanagaraj; Sridhar, Jandrajupalli; Chander Sharma, Kailash; Jain, Lata; Senthil‐Nathan, Sengottayan; Hunter, Wayne Brain; Kumar, Jagdish; Kaushal, Pankaj
Abstract: The yellow stem borer (YSB), Scirpophaga incertulas, is a borer pest of low‐land rice in tropical regions of the world, reducing production and productivity. Chemical control of YSB is challenging and often less effective due to its cryptic larval feeding behaviour inside the rice culm. Biological suppression of YSB, using egg parasitoid, Trichogramma japonicum, has been well demonstrated. Kairomones, that are interspecific, play a vital role in deciding biocontrol efficiency of egg parasitoid against lepidopteran pests. However, the mechanisms involved in terms of emission of long‐ and short‐chain volatile chemicals from YSB and its by‐products and YSB damaged rice plants in attraction to T. japonicum to locate eggs of YSB are still poorly understood. In order to trace out the volatile compounds responsible for attraction of egg parasitoid, the hexane extract of YSB female whole body and acetone extract of YSB damaged rice culm were subject to GC‐MS analyses. Out of 20 chemicals, four chemicals belonging to carboxyl, alkane and saturated fatty acid [n‐hexadecanoic acid (palmitic acid), tetradecane, octadecane, n‐octadecanoic acid (stearic acid)] from female YSB hexane extract and three sesquiterpenoids (β pinene, α pinene and caryophyllene) from YSB damaged rice plant extracts were detected in greater concentrations. In laboratory assays with the synthetic form of seven chemicals, three, n‐hexadecanoic acid, n‐octadecanoic acid and octadecane, were promising in enhancing the parasitic activity of T. japonicum on YSB eggs from 26.4% to 92.6% at 200 ppm, 27.3% to 96.5% at 500 ppm and 23.6% to 82.8% at 500 ppm, respectively, in contrast to untreated eggs (87.3% at 7 th day after exposure) and hexane washed eggs (16.7% at 7 th day after exposure). Evaluation of these compounds revealed the key chemical cues of biocontrol potential (n‐hexadecanoic acid, n‐octadecanoic acid and octadecane) for enhancing egg parasitism activity of T. japonicum on YSB eggs.